GLACIAL HISTORY WITH SPECIAL REFERENCE TO THE PAST LACUSTRINE DEPOSITS IN THE MT. RIISER-LARSEN AREA, ENDERBY LAND, EAST ANTARCTICA - ハヤシ, マサヒサ; HAYASHI, Masahisa (National Institute of Polar Research, 1990)
P(論文) The Mt. Riiser-Larsen area consists of ice-free mountains as one of the isolated massifs of the Tula Mountains, Enderby Land. Landforms and glacial history have been studied in this area with special reference to the past lacustrine deposits, "Richardson Clay". Glacial deposits of this area were divided into three groups; Tula Moraine, and Mt. Riiser-Larsen Moraines I and II. The glacial history of this area is summarized as follows : The ice sheet flowing from east to west had once covered entirely this area at its maximum stage. After the retreat from the mountain tops, the ice sheet terminated at the foot of mountains for a long time, when the Tula Moraine was deposited as ground moraine. During the subsequent warmer stage, the transgression exceeding 50m above the present sea level occurred, which resulted in joining the sea to a marginal lake with a shallow threshold. The Richardson Clay, past glacial varves, lay on the bottom of this lake. This event would have been completed prior to the late Wisconsin Glaciation. Subsequently, the sea level lowered and local alpine glaciers formed Mt. Riiser-Larsen Moraines I and II. There was no evidence that the ice sheet had expanded more extensively than the present aspect since the deposition of the Tula Moraine. This glacial history is quite correlative to those of the Vestfold Hills and the Prince Olav Coast, East Antarctica. A raised beach about 3m in altitude and a fluvioglacial channel in this area were inferred to have been formed during the Holocene. departmental bulletin paper